Influence of Water Activity, Temperature, and Their Interaction on Germination of Verticillium albo-atrum Conidia - Mozumder, Bimal K. Guha (1970)
Conidia were germinated at three temperatures in media in which available water, expressed as water activity, was controlled at three levels. Rate of germination in the basal medium (0.9964 water activity) was most rapid at 25 C and was inhibited at 15 and 30 C. Lowering the water activity at a particular temperature decreased rates of germination. However, at a low water activity (0.9778) germination rate was greater at 30 C than at 25 C. Thus, the effect of temperature on germination appears to be dependent on the water activity of the medium.